Formation of supply chains on the basis of socially responsible marketing and sustainable development - Козин, Лариса Володимирівна (Technology audit and production reserves, 2016)
The research is conducted to examine the issues of supply chains’ formation on the basis of socially responsible marketing and sustainable development. Despite the significant amount of scientific work carried out in this area, it is too complex and multilateral and needs further development. In particular, the study highlighted a basic goal of sustainable and responsible supply chain of an enterprise. It is to create, support and develop environmental, social and economic efficiency for all stakeholders that are involved in the supply of products and services to the market in the long term perspective. The role of partnership with contractors in a system of efficient market activity is grounded. On this basis, a general model of socially responsible supply chain is developed. Its key idea lays in the transformation of business processes towards the establishment of an appropriate system of governance and support of contractors in their approaching the standards of sustainability and responsibility as well as the integration of such criteria at the heart of relationships with partners. The theme of this study is inexhaustible and leaves broad opportunities for further development.